2009
DOI: 10.1083/jcb.200812176
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin regulates cofilin and N-WASp activities to control the stages of invadopodium assembly and maturation

Abstract: Invadopodia are matrix-degrading membrane protrusions in invasive carcinoma cells. The mechanisms regulating invadopodium assembly and maturation are not understood. We have dissected the stages of invadopodium assembly and maturation and show that invadopodia use cortactin phosphorylation as a master switch during these processes. In particular, cortactin phosphorylation was found to regulate cofilin and Arp2/3 complex–dependent actin polymerization. Cortactin directly binds cofilin and inhibits its severing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
486
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(518 citation statements)
references
References 49 publications
26
486
0
6
Order By: Relevance
“…3E). Cortactin binding to cofilin inhibits cofilin severing of actin filaments (12,13). We observe a similar effect, but with significantly higher concentrations of cofilin than cortactin suggesting an alternative mechanism, possibly mediated through structural changes to the actin filament.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…3E). Cortactin binding to cofilin inhibits cofilin severing of actin filaments (12,13). We observe a similar effect, but with significantly higher concentrations of cofilin than cortactin suggesting an alternative mechanism, possibly mediated through structural changes to the actin filament.…”
Section: Discussionsupporting
confidence: 61%
“…One important Arg substrate is cortactin, an actin-binding protein that stimulates the Arp2/3 complex to nucleate actin filament branches (9 -11). Cortactin also stabilizes actin filament branches (9) and inhibits actin filament severing by cofilin (12,13).…”
mentioning
confidence: 99%
“…1B). Because it is known that phosphorylation of cortactin Y421 is important for invadopodium precursor formation (Oser et al, 2009), the lower affinity of Fyn-MER for cortactin might partly explain its lower efficacy in podosome formation. We also found that the intracellular localization of Src and Fyn was appreciably different.…”
Section: Analysis Of the Initial Events Induced By Src Activation Usimentioning
confidence: 99%
“…Stress fibers are disrupted in cells with podosomes and invadopodia, whereas FAs associate and assemble with stress fibers (Carragher and Frame, 2004;Gimona and Buccione, 2006;Schoenwaelder and Burridge, 1999). Furthermore, podosomes and invadopodia specifically contain cortactin, N-WASP and Tks5 (also known as Fish), all of which can serve as substrates for Src family kinases (Mizutani et al, 2002;Oser et al, 2009;Seals et al, 2005;Suetsugu et al, 2002). Cortactin and N-WASP are required for actin remodeling during invadopodium formation (Luxenburg et al, 2006b;Mizutani et al, 2002;Yamaguchi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These effects were associated with an inability to form protrusive matrix-degrading invadapodia structures, which previous research has shown to be dependent on F-actin stabilization. [19][20][21] Not only did LIMK inhibition result in an overall decrease in F-actin staining intensity, but fluorescence recovery after photobleaching (FRAP) experiments revealed that F-actin stability was significantly reduced. As a result, we concluded that at least one way that LIMK inhibition impaired the ability of cells to lead collective invasion was through reduced F-actin stability, which directly impacted upon the ability of cells to degrade matrix.…”
mentioning
confidence: 99%